(untitled) (Journal of Engineering, 2010)
Many researches assigned the importents of enhance the architectural education movement. It is obvious that these studies have elaborated in their interest in architectural curriculum and teaching methodm in addition to the important of qualifying the staff to cover these changes. Most of these studies couldn’t define a specific solutions to improve teachers method to lead the digital education According to this the research problem was defined as: "There is no comprehensive study clear the real attitude of the architectural teachers in Iraqi schools of architecture from the digital teaching…within the vocabulary of (digital knowledge– desire for more information about digital knowledge - the attitude of digitalizing architectural curriculum between accepting and denying – employing this technolgly on selected sample)". Thus the research goal is defined as: "Give a clear vision about architectural teacher attitude in Iraqi schools of architecture in relating to to discover his real preparation to employ his knowledge using the digital technology in developing the architectural education in general, and applying their concepts in department of architecture in particular. In order to "built the propitiate mechanism in which may be used to activate this technique in Iraqi schools of architecture ". Reviewing architectural teaching curriculum and the degree which it may send for the digital education vocabulary, and define the most important ways to employ them , reviewing the studies about the reality of digital learning in Iraqi schools of architectural and analyzing the results and compare them between the architectural schools attitude the conclusions and recommendations in order to qualify them in activating the digital education technique in these schools